The Upper Siwaliks east of Jhelum, Pakistan: A new large Quaternary mammal assemblage from the Pabbi Hills and reconnaissance near Bhimbar. (10th December 2020) - Khan, Muhammad Akbar; Dar, Fatima Yousuf; Flynn, Lawrence John; Abbas, Sayyed Ghyour; Babar, Muhammad Adeeb; Akhtar, Muhammad; Zahra, Huma; Amanat, Humaira
Abstract: A new Pleistocene site in the Pabbi Hills of Pakistan, and deposits to the east near Bhimbar provide important additions to the Upper Siwalik fauna of South Asia. The mammalian fauna of 10 species from Panjan Sher Shahana at the southwestern tip of the Pabbi Hills is a rich mammalian assemblage dating to the early to Middle Pleistocene of the Upper Siwalik Subgroup. The Panjan Sher Shahana assemblage shows strong resemblance to other Pleistocene faunas of the Siwalik Group from the Indian subcontinent. The new site is dominated by Bovidae and Equus . Among megafauna, two species of Elephas, commonly found in the Upper Siwaliks, are associated with the uncommon Stegodon in Pabbi Hills. These and other elements of the Panjan Sher Shahana fauna are treated briefly here. The Late Neogene deposits of Bhimbar, 30 km east of Jhelum, appear to represent a similar succession equivalent to the Pleistocene ("Pinjor") fauna and produce important new elements, including a rare record of the bamboo rat Anepsirhizomys opdykei .